2011
DOI: 10.1093/carcin/bgr011
|View full text |Cite
|
Sign up to set email alerts
|

LOH and copy neutral LOH (cnLOH) act as alternative mechanism in sporadic colorectal cancers with chromosomal and microsatellite instability

Abstract: Our results suggest that in addition to classical LOH, cnLOH is an important mutational event in relation to the carcinogenesis of MSS and MSI tumors, causing the inactivation of a tumor suppressor gene without copy number alteration of the respective region; this is crucial for the development of MSI tumors and for some chromosomal regions in MSS tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
38
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 22 publications
7
38
0
Order By: Relevance
“…Furthermore, recent array based investigations have found MSI cancers with DNA copy number changes in unique regions of the genome [61], [62], [63], as well as copy neutral LOH events [64], [65]. By furthering this type of experimental approach, the relationship between MSI and CIN will be better understood.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent array based investigations have found MSI cancers with DNA copy number changes in unique regions of the genome [61], [62], [63], as well as copy neutral LOH events [64], [65]. By furthering this type of experimental approach, the relationship between MSI and CIN will be better understood.…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies using cytogenetic analysis have found MSI cell lines and cancers to have a considerable presence of chromosomal aberrations, predominantly cnLOH events [27], [28], [29], [30]. Similarly, studies have reported the presence of CIN and CIMP to be inversely correlated [31], [32], and the incidence of frequent methylation to be associated with reduced rates and lengths of CNAs [33], [34], [35].…”
Section: Introductionmentioning
confidence: 99%
“…Recently developed single nucleotide polymorphism (SNP) microarrays have facilitated LOH studies because they allow simultaneous detection of copy number and genotype changes. Melcher et al (33) used SNP arrays to examine and compare genome-wide LOH in CIN and MSI tumors. CIN tumors displayed mostly classic LOH (mutation followed by allele loss) at multiple genomic sites, whereas MSI tumors displayed LOH that was mostly copy-neutral.…”
mentioning
confidence: 99%